Impasses na constituição subjetiva de crianças com deficiência visual congênita - Sieiro, Aline Accioly (2013)
The social movement of Inclusion has become very powerful lately. Having its focus in inclusive processes occurred from functional adaptations in a pre established way, its emphasis has been kept on the impairment itself instead of on the subject whose deficiency becomes just something to be analyzed. This relational rigidity results in a social discourse that understands children through given signifiers considering their deficiency first and it makes difficult a subject of desire to appear as someone other then ones deficiency. Thus, having in mind the psychoanalytical method and theory, specially that one discussed by Lacan, we aim at questioning issues concerning to visual impairment within the subjective constitution of a child. Taking into account that the subjective assumption occurs in a process through which the Other is a supporting basis, we approach some fundamental concepts about subjective constitution which can be the basis for articulating the tension related to the subject and the Other in this process. Finally we aim at puzzling a possible emergence of a subject when one is marked by a visual impairment in his or her body (of language).